Bioceramic-Based Root Canal Sealers: A Review - Afaf AL-Haddad; Zeti A. Che Ab Aziz (International Journal of Biomaterials)
Bioceramic-based root canal sealers are considered to be an advantageous technology in endodontics. The aim of this review was to consider laboratory experiments and clinical studies of these sealers. An extensive search of the endodontic literature was made to identify publications related to bioceramic-based root canal sealers. The outcome of laboratory and clinical studies on the biological and physical properties of bioceramic-based sealers along with comparative studies with other sealers was assessed. Several studies were evaluated covering different properties of bioceramic-based sealers including physical properties, biocompatibility, sealing ability, adhesion, solubility, and antibacterial efficacy. Bioceramic-based sealers were found to be biocompatible and comparable to other commercial sealers. The clinical outcomes associated with the use of bioceramic-based root canal sealers are not established in the literature.